The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/6238978
|View full text |Cite
|
Sign up to set email alerts
|

Examining Relationships between Metabolism and Persistent Inflammation in HIV Patients on Antiretroviral Therapy

Abstract: With the advent of antiretroviral therapy (ART), HIV-infected individuals are now living longer and healthier lives. However, ART does not completely restore health and treated individuals are experiencing increased rates of noncommunicable diseases such as dyslipidemia, insulin resistance, type 2 diabetes, cardiovascular disease, and nonalcoholic fatty liver disease. While it is well known that persistent immune activation and inflammation contribute to the development of these comorbid diseases, the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 211 publications
0
44
0
1
Order By: Relevance
“…HIV-1 selectively infects CD4 T cells with high levels of oxidative phosphorylation and glycolysis, independently of their activation phenotype. In a similar way to carcinogenesis, it is also now admitted the existence of a metabolic reprogramming upon HIV infection, related to modifications in glucose metabolism (Ahmed et al, 2018).…”
Section: Metabolic Reprogramming Of Immune Cells In Atmentioning
confidence: 97%
“…HIV-1 selectively infects CD4 T cells with high levels of oxidative phosphorylation and glycolysis, independently of their activation phenotype. In a similar way to carcinogenesis, it is also now admitted the existence of a metabolic reprogramming upon HIV infection, related to modifications in glucose metabolism (Ahmed et al, 2018).…”
Section: Metabolic Reprogramming Of Immune Cells In Atmentioning
confidence: 97%
“…The use of ART to control HIV-1 has been associated with a number of cellular changes [44][45][46][47]. Since EpKS patients in our cohort had varying ART duration and some with detectable plasma HIV-1 viral load despite ART treatment, we tested the effect of ART duration and HIV-1 viremia on EpKS transcriptome profiles.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Whether the same dysregulations, or similar magnitude of changes, occur in EnKS, has not been investigated. Because lipid metabolic dysregulation is common in ART treated HIV-1 infected individuals [44][45][46][47], it will be important to determine whether the KS-associated lipid metabolism defects are due to KSHV infection, attributable to HIV-1 co-infection or result from ART. Moreover, a male gender bias in KS has been noted, especially for classical and EnKS, suggesting a potential involvement of androgens or androgen receptors in the disease pathogenesis [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been observed that there is a growing concern among patients with T2D to find the right line of treatment when they find themselves as HIV positive. Since T2D is associated with many other complications, treating these patients with the right combination of cART needs more collaborative approaches among clinicians in order to avoid multiorgans related complications [94,95].…”
Section: Prevalence and Incidence Rates Of T2d In The Rio Grande Valleymentioning
confidence: 99%